Simultaneous Regional Elections and Their Relevance to National Defense - Surya Iman Wahyudi; Priyanto; Afrizal Hendra (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2026)
This study examines Simultaneous Regional Head Elections in Indonesia and their role in strengthening local democracy and national defense. The objective is to analyze their impact on political stability, social cohesion, and national security. A qualitative literature review method was used by analyzing relevant sources on elections, democracy, and national resilience. The findings show that simultaneous regional elections enhance democratic processes, transparency, accountability, and good governance at the local level. However, challenges such as political tensions, social polarization, and potential conflicts may threaten stability. The study concludes that simultaneous regional elections contribute to national defense by supporting a stable and accountable governance system. Continuous political education and strict oversight are needed to ensure their effectiveness in strengthening Indonesia’s national resilience.